Evaluation of Water Content in Milk Using Microwave Transmission Approach with Horn Antenna - Ashok. Ja; Kiran Patil (Institute of Advanced Engineering and Science, 2018)
As the diary industries delivery the milk to consumer bottles in pouches the thickness of the milk is varied with each company. The microwave transmission line approach with horn antenna is introduced as an effective method for the assessment of milk for the first time with different frequency. The electrical permittivity is an intrinsic parameter of a material that can be used as an index of delivered water content. For the permittivity calculation, we use horn antenna transmitter and receiver in microwave frequency .The microwave travelled via the milk according to its thickness. A design of horn antenna and its minimum distance transmission length is followed to evaluate the thickness of milk. The dissipated power is calculated with the help of VSWR meter in decibel. The results are plotted with different microwave frequency with unique wave length with unique concentration of water with milk. Mat lab is used to plot the graph. The effects exhibit that the milk thickness makes the wave travel of microwave produces the decibel value changes at the output. The measurements demonstrate that the permittivity of milk increases with increased added water. A relationship between the added water content and the permittivity of milk -water mixture is established, which should be a powerful tool for detecting milk thickness.